A heterometallic sodium(i)–europium(iii)-organic layer exhibiting dual-responsive luminescent sensing for nitrofuran antibiotics, Cr2O72− and MnO4− anions. Issue 5 (16th January 2019) - Xu, Shan; Shi, Jing-Jing; Ding, Bo; Liu, Zheng-Yu; Wang, Xiu-Guang; Zhao, Xiao-Jun; Yang, En-Cui
Abstract : A red-emitting layer constructed from Eu2 Na(CH3 COO)2 chains and 4, 4′-(pyridine-2, 6-diyl)dibenzolate linkers exhibits luminescent discriminations for three nitrofuran antibiotics and toxic Cr2 O7 2− and MnO4 − anions. Abstract : The detection of nitrofuran antibiotics and toxic inorganic anions is currently necessary and challenging because their abuse and/or residuals have caused severe environmental pollution and illness. A heterometallic two-dimensional (2D) layered complex, [Eu2 Na(Hpddb)(pddb)2 (CH3 COO)2 ]·2.5(DMA) n (1 ), was solvothermally synthesized and structurally and photophysically characterized. Pairs of acetate aggregated Eu2 Na(CH3 COO)2 chains are periodically interconnected by V-shaped 4, 4′-(pyridine-2, 6-diyl)dibenzolate (pddb) linkers. More interestingly, the layered complex exhibits a bright red emission and can efficiently discriminate nitrofuran antibiotics by luminescent quenching with a strong quenching constant ( K sv ) and low detection limit (LOD) of 4.93 × 10 4 M −1 and 0.64 μM for nitrofurazone, 4.42 × 10 4 M −1 and 0.68 μM for nitrofurantoin as well as 2.13 × 10 4 M −1 and 1.06 μM for furazolidone. Additionally, 1 can also probe trace amounts of toxic Cr2 O7 2− and MnO4 − anions with K sv = 6.45 × 10 3 M −1 and LOD = 5.35 μM for Cr2 O7 2− and K sv = 2.84 × 10 3 M −1 and LOD = 5.99 μM for MnO4 − anions. These interesting results indicate that heteromatallic coordination polymers can serve as favorable dual- or even multiple-responsive luminescence sensors to selectively recognize different kinds of contaminants.